Some strategies for improving the accuracy of unemployment rate forcasts in România - BRATU (SIMIONESCU), Mihaela (Annals of Spiru Haret University. Economic Series, 2012)
This study proposed to evaluate some alternative forecasts for the unemployment rate of Romania made by European Commission and two national institutions: National Commission for Prognosis (NCP) and Institute for Economic Forecasting (IEF). The most accurate predictions on the forecasting horizon 2001-2011 were provided by IEF and the less accurate by NCP. These results were obtained using U1 Theil’s statistic and a new method that has not been used before in literature in this context. The multi-criteria ranking was applied to make a hierarchy of the institutions regarding the accuracy and five important accuracy measures were taken into account at the same time: mean errors, mean squared error, root mean squared error, U1 and U2 statistics of Theil. The combined forecasts of institutions’ predictions are the best strategy to improve the forecasts accuracy. The filtered and smoothed original predictions based on Hodrick-Prescott filter, respectively Holt-Winters technique are a good strategy of improving the accuracy only for NCP expectations. The assessment and improvement of forecasts accuracy have an important contribution in growing the quality of the decisional process.